Orbitofrontal syndrome in an offender incarcerated for aggravated kidnapping, rape and death of a minor - Salvatierra , Andreé (2023)
Orbitofrontal syndrome is characterized by disinhibition, impulsiveness, transgression of social norms and sometimes thedevelopment of criminal behavior. This is the case of an 18-year-old male offender incarcerated for kidnapping, rape andhomicide of a minor. He was evaluated through interviews and the use of the Eysenck personality questionnaire (Form B), Raven’s progressive matrices (RPM), Rey–Osterrieth complex figure (Form A), Differences perception test (FACES-R), Stroop color and word test (SCWT), Mini-Mental state examination (MMSE) and Aggression questionnaire (AGQ). The research subject showed age-appropriate speech, language and vocabulary, and had neither physical problems nor attention, language, writing, reading, praxis, calculation, perception and memory disorders. The results highlight a higher-than-average intelligencequotient, optimal cognitive skills, melancholic temperament with depressive thoughts, introverted personality with lowenvironmental sensitivity, poor social skills, self-absorption and avoidance. Additionally, perfectionist tendencies, suddenemotional changes, difficulty changing behavioral patterns, impulsiveness and disinhibition, all of which are characteristicsof orbitofrontal syndrome. Finally, the research highlights the use of psychometric tests and neuropsychological evaluationsfor the diagnosis of orbitofrontal syndrome. Said tests and evaluations are necessary for the proper management of offendersincarcerated in prisons and/or detention centers who do not have access to neuroimaging; moreover, they may be used to design strategic intervention programs.